Study of the prevailing morbidities in geriatric women living in an urban slum in Mumbai, Maharashtra, India - Chaudhari, Ravindra G.; Srivastav, Manissha; Hiwarkar, Yogita A. (International Journal Of Community Medicine And Public Health, 2016)
Background: Longevity has increased worldwide. This can be attributed to improved food and nutrition developments in health, and better sanitation. Old age brings in its wake, a lot of chronic ailments. Women, particularly in India, and are hard hit, due to gender marginalization. The objectives of the study were, the present study was undertaken in an urban slum in Mumbai to determine prevalence of health morbidities in geriatric women. Methods: A cross-sectional study was carried out during the period of Aug. 2008 to Nov. 2009 in the urban field practice area of Medical College in Mumbai. A total of 336 elderly consenting women above 60 years of age, were enrolled in the study. Pre-designed and pre-structured questionnaire was used for data collection. Data were analysed by using the SPSS software version-16. Results: Depression (50.8%) followed by hypertension (38.4%) was seen to be the commonest prevalent morbidities next commonest being 24 (17.39%) cataract, while 15(10.86%) had joint pain; 10 (7.24%) had diabetes, 7 (5.07%) had suffered from stroke, 06 (4.34%) had bronchial asthma, 05(3.62%) had ischemic heart disease, 04 (2.89%) had fracture, 04 (2.89%) suffered from deafness and (0.72%) had been diagnosed as diabetes. Conclusions: Community based screening programmes and subsequent interventions are urgently recommended to meet the need of this vulnerable age group.